2019
DOI: 10.1007/s40430-018-1542-5
|View full text |Cite
|
Sign up to set email alerts
|

Weldability and shear strength feasibility study for automotive electric vehicle battery tab interconnects

Abstract: Lithium-ion-based secondary battery packs are emerging as an alternative power source and are being increasingly used in electric vehicles, hybrid or plug-in hybrid electric vehicles. Typically, a standard automotive battery pack consists of hundreds, even thousands, of individual cells which are connected in series and/or parallel to deliver the required power and capacity. There is an increasing need for manufacturing of battery packs to meet the demand reflecting the uptake of these vehicles. This triggers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…For example, comprehensive research has been undertaken focusing on Li-ion battery chemistry, power capacity improvements, material development, modelling and simulation, performance enhancements or battery testing and characterisation, and safety [9][10][11]. However, the joining aspects of the Li-ion cells are mainly limited to metallurgical and mechanical characterisation of joining process [12][13][14]. There are a few literature available focusing on the comprehensive performance, characterisation and modelling of electrical resistance and thermal behaviours of the tab to bus-bar joints.…”
Section: Introductionmentioning
confidence: 99%
“…For example, comprehensive research has been undertaken focusing on Li-ion battery chemistry, power capacity improvements, material development, modelling and simulation, performance enhancements or battery testing and characterisation, and safety [9][10][11]. However, the joining aspects of the Li-ion cells are mainly limited to metallurgical and mechanical characterisation of joining process [12][13][14]. There are a few literature available focusing on the comprehensive performance, characterisation and modelling of electrical resistance and thermal behaviours of the tab to bus-bar joints.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Li-ion batteries are progressively being used for large-scale energy storage systems for grid applications [5]. As a consequence, there is substantial demand for battery manufacturing which involves a large number of individual cells to be connected either in series or parallel to deliver the required power and driving range [6]. For example, the widely used pouch cell format uses a tab-to-busbar connection as the electrical interconnect.…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely accepted joining methods to connect the pouch cell tab to the busbar is ultrasonic metal welding (UMW) due to several advantages, including joining of dissimilar materials of varying thickness, joining of highly reflective and conductive material, multiple stack-ups and low thermal input during the welding [6,13]. Li-ion battery packs for General Motors' (GM) Chevy Volt and the Nissan LEAF are currently being manufactured using UMW where the pouch cell tabs are connected with busbars [6,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Das, et al [2] have identified the suitable joining methods for cylindrical cell based battery pack building of which laser welding, micro-TIG welding and ultrasonic wedge bonding are the preferred joining methods. As dissimilar thin material joining is one of the key requirements for battery joining applications, several joining techniques are adopted to make satisfactory dissimilar interconnects, including ultrasonic metal welding [4], [5], ultrasonic wedge bonding [6], resistance spot welding [7], [8], soldering [9], micro-TIG welding [7], [10], micro-clinching [11] or laser welding [12]. Among these joining methods, laser welding provides several advantages over other joining methods including easy automation, contactless one-sided joining, high throughput, less heat input etc.…”
Section: Introductionmentioning
confidence: 99%